The organizational ecology of ethnic cleavages: The nonlinear effects of ethnic diversity on party system fragmentation. (March 2015) - Raymond, Christopher D.
Abstract: The conventional wisdom regarding party system fragmentation assumes that the effects of electoral systems and social cleavages are linear. However, recent work applying organizational ecology theories to the study of party systems has challenged the degree to which electoral system effects are linear. This paper applies such concepts to the study of social cleavages. Drawing from theories of organizational ecology and the experience of many ethnically diverse African party systems, I argue that the effects of ethnic diversity are nonlinear, with party system fragmentation increasing until reaching moderate levels of diversity before declining as diversity reaches extreme values. Examining this argument cross-nationally, the results show that accounting for nonlinearity in ethnic diversity effects significantly improves model fit. Highlights: Challenges assumptions of linear cleavage effects. Applies organizational ecology to the study of cleavages. This provides a generalizable theory of ethnic cleavage effects. Nonlinear relationship between ethnic diversity and party system fragmentation.